Effects of heat-killed Lactococcus lactis subsp. lactis JCM 5805 on mucosal and systemic immune parameters, and antiviral reactions to influenza virus in healthy adults; a randomized controlled double-blind study. (August 2017) - Fujii, Toshio; Jounai, Kenta; Horie, Akira; Takahashi, Hitoshi; Suzuki, Hiroaki; Ohshio, Konomi; Fujiwara, Daisuke; Yamamoto, Norio
Highlights: A randomized, double-blind controlled trial in 111 healthy subjects was performed. Lactococcus lactis JCM 5805 significantly up-regulated secreted IgA levels in saliva. L. lactis JCM 5805 up-regulated the phagocytotic activity of neutrophils. L. lactis JCM 5805 enhanced antiviral gene expression in PBMCs. Abstract: We investigated the effect of oral administration of heat-killed Lactococcus lactis subsp. lactis JCM 5805 (JCM5805) cells on systemic and mucosal immunological parameters. One hundred and eleven volunteers were assigned into 2 groups receiving either heat-killed JCM5805 or placebo for 4 weeks. The results suggested that secretory IgA levels in saliva were significantly increased in the JCM5805 group but not in the placebo group. Phagocytic activity of neutrophils was significantly reduced in the placebo group but not in the JCM5805 group. The severity of sore throat was lower in the JCM5805 group compared to the placebo group. The effect of JCM5805 on antiviral responses against human influenza A/H1N1 and A/H3N2 viruses was also studied and IRF7, MX1, and OAS1 in PBMCs were significantly reduced in the placebo group but not in the JCM5805 group. The effects of JCM5805 on gene expressions were significant in vaccinated subjects compared with unvaccinated subjects.